Acetylcholinesterase inhibitors for treating dementia symptoms - a safety evaluation. Issue 9 (2nd September 2017) - Mohammad, Dana; Chan, Parco; Bradley, Janelle; Lanctôt, Krista; Herrmann, Nathan
ABSTRACT: Introduction : The prevalence of Alzheimer's disease (AD) continues to rise, while treatment options for cognitive impairment are limited. Acetylcholinesterase inhibitors (AChEIs) aim to provide symptomatic benefit for cognitive decline, however these drugs are not without adverse events (AEs). The safety profile of each drug must be taken carefully into consideration before being prescribed, as new dosages and formulations have recently been approved. Areas covered : Donepezil, galantamine and rivastigmine are the three AChEIs approved for the treatment of varying stages of AD. Numerous clinical trials and post-marketing studies have evaluated the safety of these medications. This article will review the safety, efficacy and tolerability of these drugs in treating AD. Topics including pharmacovigilance databases, concomitant drug interactions, prescribing cascades, and treatment discontinuation are also covered. Expert opinion : AChEI use in those with mild, moderate or severe AD provide modest improvements in cognition, function and behavior. The pharmacological treatment of AD using AChEIs is associated with generally mild AEs. Differences in drug formulations should be taken into account when determining the most appropriate route of administration for each individual. Furthermore, discontinuation of AChEIs must be carefully monitored as it may be associated with worsening cognitive impairment.